Effect of revascularization on exercise-induced changes in cardiac and pro-thrombotic biomarkers in patients with coronary artery disease. (14th October 2021) - Hansen, C H; Cwikiel, J; Bratseth, V; Arnesen, H; Flaa, A; Seljeflot, I
Abstract: Introduction: Exercise-induced increase in cardiac and pro-thrombotic biomarkers have previously been shown in patients with coronary artery disease (CAD) before revascularization, which may be due to myocardial ischemia. Purpose: We aimed to examine whether resting levels and exercise-induced changes of high sensitive cardiac Troponin T (cTnT), NT-proBNP, pro-thrombin fragment (F) 1+2, D-dimer, tissue factor pathway inhibitor (TFPI) and endogenous thrombin potential (ETP) were affected by revascularization in patients with CAD. We hypothesized that resting and exercise-induced levels of the biomarkers would be reduced after revascularization. Methods: Patients presenting with symptoms of CAD were included. A maximal exercise ECG stress test (EST) (EST1) was performed, and venous blood samples were drawn at rest and within five min after termination. All patients underwent coronary angiography. Patients (n=20) with confirmed CAD, fully revascularized with percutaneous coronary intervention (PCI) and without symptoms of angina, were invited to perform a second EST (EST2), at the same workload (median 145W), at a median of 66 days after revascularization. Mean exercise duration at both time points were 11:30 min:sec. Of the total population 15 patients were treated with PCI on stenosis located on LAD and 5 patients with stenosis on RCA. Results: Significant increase in cTnT and NT-proBNP from resting to post exercise levels at EST1 was found as expected (p<0.001, both). Also at EST2, increased levels were observed (p<0.01, both), however, not significantly different from the changes at EST1. Resting levels of cTnT at EST2 compared to EST1 were significantly higher (median 8.1 vs 7.1 ng/L, p=0.02). At both visits significant increase in D-dimer (p=0.008 and <0.001), F1+2 (p=0.009 and 0.001) and TFPI (p<0.001 and 0.001) during exercise were demonstrated, with no difference in these changes. There were no significant changes in ETP during exercise at any visit, but resting levels were reduced at EST2 vs EST1 (p<0.01). Also resting levels of TFPI were reduced at EST2 (p<0.01). Conclusion: After revascularization there was still significant increase in exercise-induced release of cardiac and pro-thrombotic biomarkers, thus revascularization does not affect the ability to release these biomarkers. Also, the higher resting levels of cTnT after revascularization indicate that revascularization per se does not affect secretion of cardiac biomarkers, probably due to the disease state. The lower resting levels of ETP and TFPI after revascularization may, however, be indicative of reduced thrombin generation potential and endothelial activation. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Stein Erik Hagens Foundation for Clinical Heart Research, Oslo, Norway